A Systematic Review of Xuezhikang, an Extract from Red Yeast Rice, for Coronary Heart Disease Complicated by Dyslipidemia. (12th April 2012) - Shang, Qinghua; Liu, Zhaolan; Chen, Keji; Xu, Hao; Liu, Jianping
Abstract : Objective . This systematic review aims to evaluate the benefit and side effect of Xuezhikang for coronary heart disease (CHD) complicated by dyslipidemia. Methods . All randomized clinical trials (RCTs) with Xuezhikang as a treatment for CHD combined with dyslipidemia were considered for inclusion. Data extraction and analyses and quality assessment were conducted according to the Cochrane standards. Results . We included 22 randomized trials. Xuezhikang showed significant benefit on the incidence of all-cause deaths, CHD deaths, myocardial infarction, and revascularization as compared with placebo based on conventional treatment for CHD. It remarkably lowered total cholesterol (TC), triglyceride (TG), and low-density lipoprotein-cholesterol (LDL-C) as compared with the placebo or inositol nicotinate group, which was similar to statins group. Xuezhikang also raised high-density lipoprotein cholesterol (HDL-C) compared to placebo or no intervention, which was similar to Inositol nicotinate and slightly inferior to statins. The incidence of adverse events did not differ between the Xuezhikang and control group. Conclusions . Xuezhikang showed a comprehensive lipid-regulating effect and was safe and effective in reducing cardiovascular events in CHD patients complicated by dyslipidemia. However, more rigorous trials with high quality are needed to give high level of evidence.